The thorn birds : the missing years - Dobson, Kevin James (Warner Bros, 1996)
Waht happened to Father Ralph de Bricassart and Meggie Cleary O'Neill during the mystery years not covered in the original 1983 smash-hit miniseries? Now every fan can be in the know. The Thorn birds: the missing years provides the spellbinding answer. Richard Chamberlain reprises the role of de Bricassart in this eventful companion piece to The Thorn Birds. The time is World Ward II. De Briscassart heroically rescues refugees in Rome, then is sent by the Vatican to the sprawling Australian sheep ranch he thought he had left behind forever. There, a fateful reunion with Meggie (Amanda Donohoe) leads to new temptations and a profound crisis: Meggie may lose custody of the beloved son conceived during the season of forbidden love the she shared years earlier with de Bricassart